Thermogravimetric Analysis of Target Inhibitors for the Spontaneous Self-Heating of Coal. Issue 8 (2nd August 2016) - Raymond, Christopher J.; Farmer, Justin; Dockery, Christopher R.
ABSTRACT: Self-oxidation of coal can result in spontaneous combustion events at any time during mining, transporting, or processing causing environmental, economical, and safety concerns. Spontaneous coal combustion is a naturally occurring phenomenon that often causes damage to industrial and commercial facilities and freight, reduces the caloric value of coal, releases noxious gases and particulate matter, and increases pollution. As heat accumulates through self-oxidation, the internal temperature of the coal continues to rise over time and if left unaltered will lead to spontaneous coal fires. In this study, we investigated thermogravimetric properties of target compounds for the inhibition of the spontaneous self-heating of coal. Coal was treated with inorganic phosphate and sulfonate salts combined with anionic and non-ionic surfactant blends. Each ingredient was applied to the surface individually and systematically varied to reach a cost-effective and efficient formulation. Thermal and microscopic analyses were used to characterize these effects. Results showed that novel formulations can significantly increase the onset temperature for pyrolysis and oxidation of coal.